Political Engineering and its Impact on the Performance of Wise Leadership in Reformation and Change - Hameed Al-Badrany, Adnan Khalaf (Opción, 2019)
Political engineering is a new science, and it is still in the process of formation, as this science develops to keep up with the developments of the times and branch out into complex subjects and branches. The science of political engineering is an integral part of political science, because rational politics requires a full understanding of societal values, ie the knowledge of the weight of the preferences of society as a whole and not part of it. They also require information on alternative policies or the ability to properly predict their results and the exact calculation of the difference between cost and return, and they finally explore a decision-making system that rationali- zes policy-making. However, the rational preparation of political engineering and reform may face some difficulties, which are often not easily overcome Political engineering is not an invitation to a dictatorial thought or a promotion of one opinion, nor is it an invitation to the meta-nature of socie- ties or people’s wills. The formulation of its vision stems from the study of all things to improve all of them, and to develop a comprehensive long-term vision that makes policies and sets the pace in the right direction.